2015
DOI: 10.2337/db15-0871
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity Impairment During Hypoglycemia: Implications for Cardiovascular Control

Abstract: Studies have shown associations between exposure to hypoglycemia and increased mortality, raising the possibility that hypoglycemia has adverse cardiovascular effects. In this study, we determined the acute effects of hypoglycemia on cardiovascular autonomic control. Seventeen healthy volunteers were exposed to experimental hypoglycemia (2.8 mmol/L) for 120 min. Cardiac vagal baroreflex function was assessed using the modified Oxford method before the initiation of the hypoglycemic-hyperinsulinemic clamp proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…BRS is helpful in assessing the development and progression of CVDs [ 25 ]. Parasympathetic component of the baroreflex was measured as the ratio of reflex bradycardia response to dose-dependent increase in mean arterial pressure (ΔHR/ΔMAP) by phenylephrine.…”
Section: Resultsmentioning
confidence: 99%
“…BRS is helpful in assessing the development and progression of CVDs [ 25 ]. Parasympathetic component of the baroreflex was measured as the ratio of reflex bradycardia response to dose-dependent increase in mean arterial pressure (ΔHR/ΔMAP) by phenylephrine.…”
Section: Resultsmentioning
confidence: 99%
“…BRS describes the degree to which the heart rate increases or decreases in response to a given change in mean arterial pressure as a consequence of the baroreflex. In detailed experimental studies of participants with and without type 1 diabetes, BRS has been shown to fall during experimental hypoglycemia along with a resetting of the working range to higher heart rates ( 29 , 30 ). In patients with diabetes, a failure of baroreceptors to reset to higher heart rates could lead to an increase in vagal restraint in the face of sustained sympathetic stimulation, rising SBP, and pulse pressure because the operating point remains at baseline levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that CAN is independently associated with hypoglycemia in patients with diabetes 25,94,95 . Several studies have also shown that hypoglycemia can promote reductions in heart rate variability and the baroreflex sensitivity in both patients with diabetes 96,97 and healthy controls 98 that might last for many hours after euglycemia is restored 97 . In addition, our group has reported that increased glucose variability, particularly with a predominance of hypoglycemic stress measures, was associated with blunting in measures of heart rate variability in type 1 diabetes patients 94 .…”
Section: Hypoglycemia and Cardiovascular Autonomic Neuropathymentioning
confidence: 99%